Development and validation of the health literacy towards dietary supplements for beauty among Thai undergraduate students - Pansathin A. (2023)
The aim of this cross-sectional study is to develop a measurement for Health Literacy towards Dietary Supplements for Beauty (HLDS) based on Sørensen’s health literacy concept. The measurement is applied to assess the health literacy of undergraduate students. The Thai undergraduate students participating in the study are in years 1–4 at a university in Bangkok. Data collection is performed via a self-administered questionnaire. The following techniques are used in this study to investigate the construct validity of the measurement: confirmatory factor analysis, convergent validity, and discriminant validity. The statistical software Analysis of Moment Structures (AMOS) version 20 is used. To develop the HLDS measurement, 31 items are derived, divided into four dimensions: Access (9 items), Understand (10 items), Appraise (4 items), and Apply (7 items). The findings revealed high discrimination values (r = 0.54-0.94) with Cronbach’s alpha coefficients ranging from good to very good (α = 0.81-0.91). The measurement model of the HLDS fits well with the empirical data. The convergent validity meets the acceptance criteria, while the discriminant validity exhibits values slightly higher than the criteria (r=0.74-0.94). Accordingly, the HLDS measurement is considered to be valid, reliable, and applicable for applying to undergraduate students. However, the addition of the social skill assessment is required to achieve a more comprehensive measurement. This skill is recognized within the process of HLDS development but with some limitations. Thus, it is recommended that this dimension be added for future study.